Maternal attitudes in relation to pre-schoolers' nutrient intake and nutritional status - Amarra, Ma. Sofia Valencia; Florencio, Cecilia A. (1991)
The study examine the relationship between mothers' child-rearing and nutrition attitudes and their preschoolers' nutrient intake and nutritional status. The independent variable was the mother's attitudes toward child-rearing and nutrition, while the dependent variables were the child's nutrient intake and nutritional status. The sample consisted of 95 children from an urban depressed community in Taytay, with ages ranging from 1 to 6 years, and their mothers. Determination of maternal attitudes was done using a Likert-type Maternal Attitude Scale (MAS) and a questionnaire on parental acceptance and satisfaction. Nutrient intake was determined by means of a three day food recall while nutritional status was assessed by means of weighing. The results indicate that mother of normal, mild, and moderately underweight children differ in their child-rearing and nutrition attitudes. Mothers of moderately underweight children were significantly more reluctant to assume the difficulties of motherhood and tended to view nutrition as unimportant in their children's lives than mothers of the normal and mildly underweight groups. There was also a significant inverse relationship between the child's weight for age and the mother's reluctance to assume the difficulties of motherhood, her view that nutrition is not important, and her dissatisfaction with the child's personal qualities. The results also showed a decline in energy intake to be significantly related to the mother's tendency to be indifferent to the child's needs and her dissatisfaction with the child's personal qualities. Mothers whose attitudes in both nutrition and child-rearing were classified as low positive had children who were moderately underweight, whereas those classified as high positive had normal or mildly underweight children. Factor analysis showed that mothers with milk and moderately underweight children had similar traits, while those with normal children had traits which were different from the other two groups. Among the mild and moderately underweight groups, negative child-rearing attitudes accounted for a larger percentage of the variance in weight than positive attitudes and the sex of the child was closely associated to the mother's pregnancy and their emotion upon learning that she was pregnant. Mothers of normal children planned and welcomed their pregnancies more than mothers of the mild and moderately underweight groups did. Based on the results of the study, it can be concluded that maternal attitudes in both child-rearing and nutrition are significantly related to the child's weight for age and his energy intake per kilogram body weight. Mothers of moderately underweight children had certain child-rearing and nutrition attitudes which differed significantly from those of the other two groups. In terms of personality traits, however, mothers of the moderately underweight group were more similar to those with mildly underweight children than those with normal children.
Computer print-out.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Preschool children -- Philippines -- Rizal -- Taytay -- Nutrition; Mothers -- Philippines -- Rizal -- Attitudes